Comparison of the effectiveness of 5-Fluorouracil and modified Carnoy's solution in reducing the recurrence of odontogenic keratocyst - Sandip A. Wanve; Neelam N. Andrade; Lakshmi Venkatakrishnan; Harsh Desai (Elsevier, 2023)
Introduction: Odontogenic keratocysts (OKC) has a high potential for recurrence. Resection is currently the only fool-proof method to ensure that recurrence does not occur; however, it drastically affects the patient's function and aesthetics. Application of modified Carnoy's solution (MCS) as an adjunct to reduce the recurrence rate is currently in vogue. 5- Flurouracil (5-FU) is an anti-metabolite that has been used in the treatment of basal cell carcinoma and is relatively safer than MCS. The present study aims to compare the effectiveness of 5-UC and MCS in reducing the recurrence rate in OKC.. Material and methods: A total of 42 OKCs were enucleated followed by application of MCS (control group, n = 21) or 5-FU dressing (study group, n = 21) following enucleation. Pain, swelling, temporary and permanent paresthesia paresthesia, bone sequestrum formation, osteomyelitis and recurrence in both groups were evaluated at periodic intervals up to 12 months post-surgery. Results: There was no significant difference in terms of pain, or swelling in both groups. Permanent paresthesia and recurrence rates were higher in patients treated with MC but the difference was not statistically significant. Conclusion: 5-FU is an easy-to-use, feasible, biocompatible and cost-effective alternative for MCS in the management of OKCs. Treatment with 5-FU, therefore, reduces the risk of recurrence and also the post-surgical morbidity associated with other treatment procedures.